Trends and Innovations in CRM for Patient Management: A Literature Review - Muhdiantini, Cindy; Fitri Yani, Mega; Ibnu Zulkarnain (SITEKNIK: Sistem Informasi, Teknik dan Teknologi Terapan, 2025)
Customer Relationship Management (CRM) in healthcare services has evolved rapidly with advancements in information technology. CRM not only functions as a patient relationship management tool but also as a solution to enhance data-driven care, service personalization, and operational efficiency. Current trends in CRM involve the utilization of Artificial Intelligence (AI) and Machine Learning (ML), integration with wearable devices for real-time health monitoring, the use of Big Data for analyzing population health trends, as well as the adoption of telemedicine and mobile health applications connected to CRM. This study aims to review the latest developments in CRM for patient management and its impact on healthcare systems.